Implementasi Penggunaan Tes Essay dalam Evaluasi Pembelajaran Daring pada Siswa Kelas VII SMP Negeri 1 Tlanakan - Wachidah, Liana Rochmatul; Laila, Yani; Irmawati, Ayu; Amin, Shidiq (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Learning evaluation is the process of measuring and assessing learning activities, in this case the teacher measures and assesses students using test instruments. This study aims to present the results of the evaluation of bold learning using objective test instruments and explanations. This study uses a descriptive approach approach. Sources of data in this study were grade VII students of SMP Negeri 1 Tlanakan. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis technique used qualitative analysis, namely data reduction, data presentation and conclusion drawing. The results of data analysis in this study indicate that the implementation of the test instrument boldly in class VII students at SMP Negeri 1 Tlanakan is more dominantly effective using the description test. This is because by using the description test students are easier and develop their knowledge with their own reasoning. There are three obstacles for students in implementing objective and objective tests, namely (1) problems in terms of working on questions, this is due to students' misunderstandings in learning challenges, (2) constraints during implementation, students cannot ask questions that are not explained clearly. directly to the teacher, and (3) network or internet connection problems for students who live in remote areas.